2018
DOI: 10.1002/aorn.12075
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Novel Memory Aid to Educate Perioperative Team Members on Proper Patient Positioning Technique

Abstract: Interdisciplinary collaboration is key to safe surgical positioning. Although the surgical procedure dictates the patient's position, surgeons, anesthesia care providers, intraoperative nurses, and ancillary staff members must work together to achieve the goal of safe positioning. Correct patient positioning includes the provision of adequate access to the surgical site for the surgeon and surgical assistants. Surgical positions may put the patient at risk of injury. Understanding human anatomy, including the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
1
14
0
2
Order By: Relevance
“…These ndings are similar to those of other studies [25]. Previous prone position studies or training usually aim to prevent one particular complication or to introduce the prone positioning method [7,14,15], but not analyze the high-risk factors and measures during each stage of prone positioning. As a result, the nurse's prone positioning theoretical and practice level knowledge depends on their own knowledge and experience with this position.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These ndings are similar to those of other studies [25]. Previous prone position studies or training usually aim to prevent one particular complication or to introduce the prone positioning method [7,14,15], but not analyze the high-risk factors and measures during each stage of prone positioning. As a result, the nurse's prone positioning theoretical and practice level knowledge depends on their own knowledge and experience with this position.…”
Section: Discussionsupporting
confidence: 85%
“…Prior work showed that 73% of the operating room (OR) nurses did not have adequate knowledge about how to prevent perioperative PI, and their ability to identify risks for PI was also limited [6]. OR nurses also lack an evidence-based tool and method to help them provide optimal prone position nursing practices [7]. Enhancing OR nurses' skills for managing patients in the prone position is necessary to prevent injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Finally, we strongly believe that educational meetings aimed at creating a trained and expert multidisciplinary, interdepartmental team devoted to the application of a protection strategy based on matching support surfaces and prophylactic dressings to meet the PI prevention needs of the whole paediatric age range spectrum during LDSP and the subsequent post-operative period, are essential and indivisible features of a successful PI prevention program for complex vulnerable children undergoing long duration surgical procedures. [47][48][49]…”
Section: Limitationsmentioning
confidence: 99%
“…However, prior work showed that 73% of the operating room (OR) nurses did not have adequate knowledge about how to prevent perioperative PI, and their ability to identify risks for PI was also limited (Khong et al, 2020 ). Besides, they also lack evidence‐based tools and methods to help them provide optimal prone position nursing practices (Woodfin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%